Dear Mendl, Dear Reyzl : Yiddish Letter Manuals from Russia and America - Nakhimovsky, Alice S.; Newman, Roberta, 1958- (Book collections on Project MUSE., 2014)
At the turn of the 20th century, Jewish families scattered by migration could stay in touch only through letters. Jews in the Russian Empire and America wrote business letters, romantic letters, and emotionally intense family letters. But for many Jews who were unaccustomed to communicating their public and private thoughts in writing, correspondence was a challenge. How could they make sure their spelling was correct and they were organizing their thoughts properly? A popular solution was to consult brivnshtelers, Yiddish-language books of model letters. Dear Mendl, Dear Reyzl translates sele.